Humanistic challenges of modern society - Marković Savić, Olivera S. (Sociološki pregled, 2020)
In the jaws of transition: Between the Downfall and the Alternative (A Plea for the Transition of Transition and Alternative Society), the work of sociologist, professor emeritus of the University in Niš, gives an analytical contribution to the contradictions of social transition. The author bases the social critique of dehumanized neoliberal transition and offers the perspective of the society science in current national and world conditions and challenges. The analysis is focused on the poor condition of economy in the Republic of Serbia, with the emphasis on the problems of dependent modernization, class polarization and destruction of the social state. Apart from analyzing the above-listed problems, the author recommends the role of sociology as the humanistic critique of the modern society.